ANALISIS KOMODITAS UNGGULAN KOPI DI KABUPATEN OKU SELATAN - Hendri, Hendri; Sari, Yunita; Oktarina, Yetty (AGROTEKSOS; Vol 35 No 2 (2025): Jurnal Agroteksos Agustus 2025DO - 10.29303/agroteksos.v35i2.1348, 2025)
Coffee commodities are one of the important commodities in the plantation subsector. Most of Indonesia's coffee production is a plantation commodity that is exported to global markets. To address the above issues, the Location Quotient (LQ) analysis is used; LQ analysis is employed to determine basic/superior and non-basic commodities. Based on the research conducted, it was concluded that the LQ analysis of coffee commodities has an index value of 3.45 = LQ > 1, which indicates that coffee commodities in South OKU Regency are basic or superior commodities, meaning that the production sector of coffee commodities can already meet the needs of South OKU Regency.